Definition as Situated Interpretational Vector Response to Commentaries - Engler, Steven; Gardiner, Mark Q. (Aries - Journal for the Study of Western Esotericism, 2024)
This short piece responds to the sixteen commentaries included in this special issue of Aries, each of which addressed aspects of our target article, ‘(Re)defining Esotericism: Fluid Definitions, Property Clusters and the Cross-Cultural Debate’. We reaffirm our approach with a metaphor: defining is a process of guiding interpretation in a certain direction from a certain starting point; and academic disciplines, like the study of esotericism, provide especially useful contexts for situating such semantic vectors. The response addresses issues of disciplinary context, the nature of consensus and philosophical views of meaning.
Created from Fastlane, Scopus look-up
Keywords: definition; esotericism; homeostatic property cluster definition; polythetic definition; religion; semantic theory